Studying the effects of varying and phase spectrum of speech signal [electronic resource] - 191649 Hidayat Fahmi Abdul Rahim; Fakulti Kejuruteraan Elektrik (2007)
Project Paper (Sarjana Muda Kejuruteraan (Elektrik - Elektronik)) - Universiti Teknologi Malaysia, 2007